Continuous SO2 flux measurements for Vulcano Island, Italy - Vita, Fabio; Bobrowski, Nicole (Annals of geophysics, 2012)
The La Fossa cone of Vulcano Island (Aeolian Archipelago, Italy) is a closed conduit volcano. Today, Vulcano Island is characterized by sulfataric activity, with a large fumarolic field that is mainly located in the summit area. A scanning differential optical absorption spectroscopy instrument designed by the Optical Sensing Group of Chalmers University of Technology in Göteborg, Sweden, was installed in the framework of the European project "Network for Observation of Volcanic and Atmospheric Change", in March 2008. This study presents the first dataset of SO2 plume fluxes recorded for a closed volcanic system. Between 2008 and 2010, the SO2 fluxes recorded showed average values of 12 t.d-1 during the normal sulfataric activity of Vulcano Island, with one exceptional event of strong degassing that occurred between September and December, 2009, when the SO2 emissions reached up to 100 t.d-1.